Pengaruh Cita Rasa dan Harga Produk terhadap Word of Mouth (WOM) pada Konsumen Produk Healthy Boost Juice - Nor Fadhilatur Rohma; Aisyah Armistya Putri; Anisa Septia Mahardiani; Nindya Kartika Kusmayati; Nunuk Latifah (Faculty of Social and Political Science, 2026)
This study is designed to examine the effects of product taste and pricing on word of mouth (WOM) within the healthy beverage sector. A quantitative method was applied, utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM) as the analytical technique. The data were obtained from a sample of l00 respondents. The findings indicate that both taste and price have a significant impact on WOM, with taste demonstrating a more substantial influence. The analysis using the Partial Least Squares approach involves evaluating the structural model, testing construct validity, and ensuring the reliability of the measurement model. The results further reveal that higher price perceptions can enhance consumer appreciation and increase the likelihood of sharing experiences. Additionally, when consumers perceive the taste as satisfying and the price as commensurate with product quality, they are more inclined to recommend the product to others. These findings highlight that superior taste and appropriate pricing play a crucial role in strengthening customer loyalty and encouraging positive WOM in the healthy beverage industry.